Military Potential of Central and Eastern European States and Its Significance in Strengthening the EU’s Military Actorness - Borys Lesyk (Історико-політичні проблеми сучасного світу)
he role of Central and Eastern European states in the formation and strengthening of the European Union's military actorness was researched. The transformation of the region's countries from the “periphery” to the “security frontier” of the EU under conditions of Russia's full-scale invasion of Ukraine was examined. The military potential of Poland, the Czech Republic, Hungary, Slovakia, Romania, Bulgaria, Lithuania, Estonia, and Latvia, as well as their participation in Permanent Structured Cooperation (PESCO) projects, was analyzed. The distribution of specialization areas and responsibilities among the region's states was identified. Poland acts as a regional leader in terms of land forces; the Czech Republic, Hungary, Slovakia, Romania, and Bulgaria are providing the technological foundation for defense integration through the development of military-industrial complexes; the Baltic states specialize in countering cyber threats and hybrid attacks. It was established that the CEE-SEE states are gradually reorienting themselves from “consumers” to active participants in the collective defense system, which attests to their strategic value for the European Union.